The Impact of Turkish Water Policy on The Agricultural Sector in Syria - لايقة زينب; شادي شهيله (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research discusses the repercussions of the dispute between the riparian countries about the legal system of the Euphrates River on the economic reality in Syria by studying the impact of the disputes of the countries of the Euphrates River basin on Syria, especially on the agricultural sector in it, in addition to knowing the extent to which Syria was affected by the Turkish water projects established on the Euphrates River and its sustainable development. The research aimed to show the impact of Turkish water projects on the agricultural sector in Syria, by relying on the descriptive analytical approach, as Turkey’s goal of its water policy was to achieve many goals, whether political, security or economic, at the regional level. The research concluded the extent to which Turkey ignores the status of international rivers and the common legal rights in them, and attempts to extend its influence over the region, as Turkey has given absolute ownership over the rivers, especially the Euphrates River.